Falsified drugs as a challenge to public health - an attempt to define the concept and scale of the phenomenon in the world as well as legal and sociological approach - Damian Świeczkowski (Farmacja Polska, 2019)
The below article is a review regarding sociological and factual context of the implementation of Falsified Medicine Directive with a particular focus on Poland. In order to clarify the subject, a brief description of the phenomenon of falsified and counterfeit medicines, including an attempt at definition and disambiguation of those terms, is given. Further, the authors briefly describe the circumstances and effects of the implementation of the said directive in Poland. This includes outline of the solutions required and forced by the European and Polish law (serialization, anti-tempering devices, and personnel training) as well as practical information (and scientific background) on how provisions of the Directive are fulfilled in the setting of Polish community pharmacies and medicine wholesalers and which agents are responsible for the process of integration of the Directive into Polish law and reality. The presentation of the prevalence and extent of the phenomenon of falsified and counterfeit medicines in Poland and around the world includes mention of the most notable cases in the field along with research conducted and countermeasures undertook to tackle the issue. The part dedicated to review of the sociological context gives overview of the most notable of the very few research published in the field, both by Polish and foreign authors. Referenced articles describe awareness of the issue of counterfeit medicines among medical professionals and the general public. Investigated studies are immersed almost solely in the quantitative approach (authorial questionnaire used in cross-sectional studies) with a limited number of studies based on a qualitative approach, which constitutes an important gap in current knowledge. The authors conclude that counterfeit medicines pose an ever-growing threat to public health on both local and global level, that international cooperation and legislature dedicated to unification of laws aimed at counterfeit medicines, as exemplified by the said Directive, is an effective approach to the issue and that the current state of research does not allow for full understanding of patients’ perspective on the topic falsified medicines.